2020
DOI: 10.1002/slct.201903818
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Assisted Extraction of Fucoidan from Vietnamese Brown Seaweed Sargassum mcclurei and Testing Bioactivities of the Extract

Abstract: In this study, fucoidan was extracted from the Vietnamese brown seaweed Sargassum mcclurei by ultrasound -assisted extraction method (UAE) using ethanol as a solvent. The effects of single factors on total polysaccharide (TPS) content were then investigated, followed by the screening of main factors affecting TPS content based on their effect sizes and p-values in analysis of variance. The response surface methodology using the Box-Behnken design was applied to investigate simultaneous effects of four main fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The authors reported the highest extraction yield of fucoidan from conventional chemical (11.9%) and microwave-assisted (5.71%) extraction methods. In another study, fucoidan was extracted from Sargassum mcclurei brown seaweed by an ultrasound-assisted extraction method using ethanol and reported a yield of 7.1 mg/g of total polysaccharide content (representing fucoidan) in the extract [29]. The results are expressed as mean ± standard deviation of the mean (n = 2).…”
Section: Biochemical Composition Analysismentioning
confidence: 99%
“…The authors reported the highest extraction yield of fucoidan from conventional chemical (11.9%) and microwave-assisted (5.71%) extraction methods. In another study, fucoidan was extracted from Sargassum mcclurei brown seaweed by an ultrasound-assisted extraction method using ethanol and reported a yield of 7.1 mg/g of total polysaccharide content (representing fucoidan) in the extract [29]. The results are expressed as mean ± standard deviation of the mean (n = 2).…”
Section: Biochemical Composition Analysismentioning
confidence: 99%
“…55 When alcohol was used as a solvent in ultrasonic extraction, the fucoidan yield increased by 16.8%, compared to the extraction with hot water. In this way, fucoidan was obtained from Sargassum mcclurei at a solvent to algae ratio of 24:1, the extraction time of 49 min at 54°C, with the ultrasound power being 360 W. 56 Ultrasonic exposure is also known to lead to an increase in enzyme activity when used together. The enzymatic ultrasonic extraction method allows for obtaining a lower molecular weight polysaccharide with a higher fucoidan yield compared to the ultrasonic method (from 3.6% to 7.87%).…”
Section: Ultrasonic Extraction Of Fucoidanmentioning
confidence: 99%
“…In UCGE, ultrasonic energy can destroy the plant cell membrane, accelerate the molecular movement, and improve the mass transfer rate. Thus, the UCGE has been gradually applied to traditional Chinese medicine and functional foods [19–21] …”
Section: Introductionmentioning
confidence: 99%